Assessing regional competitiveness: analysis of stock indicators and flows variables - Lorenzo Giovanni Bellù; Vito Cistulli; Stefano Marta; Francesco Timpano (European Regional Science Association (ERSA), 2011)
The issue of the measurement and assessment of territorial competitiveness is of increasing importance for the determination of development strategies at all geographical levels: country, regional and cluster level. The proposed approach focuses on regional competitiveness, given the raising influence of regions as key players within the global development process. This paper is based on the analysis and development of models and tools that aims at measuring and assessing territorial competitiveness and in particular territorial assets - both tangible and intangible - responsible for the development of a region. This approach will consider the theoretical models identified by M. Porter, especially the Diamond model, which defines the factors determining regional development and the contributions of R. Martin, A. Rodríguez-Pose, A. Pike M. Caroli and R. Camagni. Moreover, the paper will take into consideration some well-known competitiveness composite indices for territorial analysis: EU Regional Competitiveness Index by JRC, the Global Competitiveness Index by WEF, the Livelihood Systems by WFP. The conceptual framework of this paper is based on the assumption that economic indicators, such as GDP, are not sufficient to explain why one territory or geographical space performs better than other surrounding territories. Other social, demographic, cultural, natural, and infrastructural factors also influence competitiveness through complex interactions. A basic conceptual objective of the paper is to integrate a synthesis Territorial Competitiveness Index, which focus on territorial assets, with a Social Accounting Matrix (SAM), that measures the economic flows within a given area (Pyatt-Round), in order to define a composite model that combines sectors' potential resulting from the multipliers based on SAM with the Index. The integration of these "stock and flows" measurement tools will enhance the approach used by enabling assessment of territorial scenarios and identification of territorial potential (both expressed and latent). The expected usefulness of this combined approach is a better understanding of comparative strengths and weaknesses of the territories, which would allow the policy makers at local and central level to better target strategies and policies, and establish a benchmarking system that would allow for comparisons among territories both within and among countries.
Keywords: 330